ANALISIS KESESUAIAN MATERI JAMUR PADA BUKU BIOLOGI DENGAN KOMPETENSI DASAR KURIKULUM 2013 - Amilil Hudi; Tri Jalmo; Arwin Surbakti (Universitas Lampung, 2018)
This study aims to describe the level of conformity of fungi material on Biology textbook of high school class X from the aspect of breadth and depth of material. The sample of this study was A book which published by Erlangga and B book which published by Yrama Widya. Data was collected from documentation technique, through content analysis ontextbook. The data of this study were suitability material of fungi intextbookthatwerereviewed from breadth and depth that were analyzed by qualitative descriptive.The result of this research shows that conformity level of fungiin A book from the aspect of breadth and depth of material were categorized